Carrier dynamics and gain in 1.3μm InGaAsN/GaAsP/GaAs laser diodes - Antón, Ovidio, author; Menoni, Carmen, advisor; Sites, James R., committee member; Pikal, J. M., committee member; Bartels, R., committee member; Maciejewski, A. A., committee member (Colorado State University. Libraries, 2006)
This dissertation investigates the impact of nitrogen incorporation on the intrinsic processes that affects the threshold current and frequency response of 1.3μm InGaAsN/GaAsP/GaAs single quantum well (SQW) lasers. This study is accomplished through the analysis of the below threshold carrier lifetime and material gain and the frequency response above threshold in two identical laser structures that only differ in the incorporation of nitrogen. The above and below threshold frequency responses results are analyzed with a complete rate equation model of the laser diode that contains intrinsic material processes as well as external parasitics associated with the diode device. The below threshold analysis coupled with the gain results provide the framework to understand the behavior of the threshold current in the 10-80°C temperature range in the nitrogen-containing structures in relation to that of the nitrogen free counterparts. This study was instrumental to find a three times increase in the monomolecular recombination and Cw parameter, and a ~30% decrease in the effective threshold differential gain in dilute nitride materials due to nitrogen incorporation. It was found that their combined effects could account for the majority of the increase in the threshold current and the decrease in the effective temperature T0 in dilute nitride lasers. The study above threshold was motivated by the need to understand the potential of the dilute nitride laser for direct high speed modulation. In these studies the frequency response of the laser diode is obtained using selective femtosecond optical injection. As an innovation to the setup, we implemented this technique with pulse bias in order to prevent device damage and to reach 80°C in the active area. We show that single quantum well InGaAsN lasers reach -3dB bandwidths of 8.5GHz at 10°C, and their bandwidth reduces by 40% at 80°C. We analyze the modulation responses to extract the resonance frequency and damping. We utilize the rate equation model that incorporates carrier transport and electrical parasitics to show for the first time that the damping is affected by parasitics even under optical modulation. Further, the model permits to study the threshold effective differential gain of the devices. Within the uncertainties of the analysis, it is found that the effective differential gain shows a decrease with nitrogen incorporation similar to that observed from the analysis below threshold and furthermore, an identical temperature behavior. The results of this work are exploited to provide guidelines into the design of optimized laser structures with temperature insensitive threshold currents and bandwidths exceeding 10GHz, outperforming the existing 1.3μm InP-based technology.
Carrier dynamics and gain in 1.3μm indium gallium arsenic nitride/gallium arsenic phosphide/gallium arsenide laser diodes
Keywords: electrical engineering; optics